Analisis Store Atmosphere Terhadap Minat beli di Kopi Keraton Cirebon - Nicolash Brandon Kusuma; Vishnuvardhana (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Kopi Keraton, located on Jalan Slamet Riyadi No. 9A, Sukapura, Kec. Kejaksan, Cirebon City West Java. It has a less store atmosphere but has a lot of visitors. The aim of this research is to see whether store atmosphere has an influence on buying interest. The research method used is a quantitative method, the population in this study are visitors to the Kopi Keraton coffee shop and consumers of the Kopi Keraton coffee shop itself. The sampling technique used is n probability sampling. The results of the research itself show that store atmosphere has an influence on buying interest from visitors and consumers from the Kopi Keraton coffee shop, therefore, Kopi Keraton needs to improve their store atmosphere so that visitors and consumers can feel more comfortable when in the coffee shop. the.